Multi-Level Effects of Humble Leadership on Employees’ Work Well-Being: The Roles of Psychological Safety and Error Management Climate - Zhang, Zheng; Song, Peng (Frontiers in Psychology, 2020)
Employees’ work well-being (WWB) is vital to employees’ performance and organizations’ sustainable development. This study aims to explore the role of psychological safety and error management climate (EMC) between humble leadership and WWB in Chinese organizations. Drawing upon social information processing theory, a multi-level study was conducted to test the underlying mechanisms between humble leadership and employees’ WWB. A time-lagged data of 221 team members was collected from 12 small and medium sized companies in China. Results showed that team-level humble leadership was positively related to WWB. Psychological safety and EMC both played a partial mediating role linking humble leadership and WWB. EMC positively moderated the relationship between humble leadership and psychological safety. This paper contributes to revealing the multi-level effects of humble leadership on work well-being. These findings also provided some important implications for managerial practices.